2005
DOI: 10.1523/jneurosci.1016-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Posthearing Developmental Refinement of Temporal Processing in Principal Neurons of the Medial Superior Olive

Abstract: In mammals, principal neurons of the medial superior olive (MSO) exhibit biophysical specializations that enable them to detect soundlocalization cues with microsecond precision. In the present study, we used whole-cell patch recordings to examine the development of the intrinsic electrical properties of these neurons in brainstem slices from postnatal day 14 (P14) to P38 gerbils. In the week after hearing onset (P14 -P21), we observed dramatic reductions in somatic EPSP duration, input resistance, and membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
229
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(266 citation statements)
references
References 59 publications
32
229
5
Order By: Relevance
“…A low input resistance contributes to the short membrane time constant, which is thought to be necessary for ITD computation (Gerstner et al, 1996). Similar low input resistance has also been reported in other auditory coincidence detectors such as the NL neurons of posthatch chicks (Kuba et al, 2005(Kuba et al, , 2006 and the mammalian MSO (Scott et al, 2005).…”
Section: Analysis Of Sapsupporting
confidence: 65%
See 2 more Smart Citations
“…A low input resistance contributes to the short membrane time constant, which is thought to be necessary for ITD computation (Gerstner et al, 1996). Similar low input resistance has also been reported in other auditory coincidence detectors such as the NL neurons of posthatch chicks (Kuba et al, 2005(Kuba et al, , 2006 and the mammalian MSO (Scott et al, 2005).…”
Section: Analysis Of Sapsupporting
confidence: 65%
“…This phenomenon has been observed in in vitro studies of NL cells in posthatch chicks (Kuba et al, 2006), neurons of the medial superior olivary nucleus (MSO) of the gerbil (Scott et al, 2005), and octopus cells of the anteroventral cochlear nucleus (Golding et al, 1999), but was not previously confirmed in vivo.…”
Section: Analysis Of Sapmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been suggested the normally-developing SOC retains the ability to calibrate ITD sensitivity to changes in head size throughout childhood but that the basic functional structure for processing interaural cues is intact very early in development (Ashmead et al 1991;Scott et al 2005). This raises the question of whether bilateral cochlear implantation provides sufficient information for the proper calibration of the SOC in congenitally deaf children.…”
Section: Physiology Of Binaural Hearingmentioning
confidence: 99%
“…Neurons in the MSO have a low input resistance (Magnusson et al, 2005;Scott et al, 2005;Chirila et al, 2007), suggesting that large synaptic currents are required for action potential (AP) generation and for inhibitory inputs to have a significant impact. This assumption is supported by ultrastructural evidence for multiple active zones on both excitatory and inhibitory synaptic boutons contacting the MSO (Clark, 1969;Lindsey, 1975;Kiss and Majorossy, 1983;Brunso-Bechtold et al, 1990;Kapfer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%